A high proportion of caseous necrosis, abscess, and granulation tissue formation in spinal tuberculosis - Wu, Runrui; Li, Shanshan; Liu, Yadong; Zhang, Hong; Liu, Dongxu; Liu, Yuejiao; Chen, Wen; Wang, Fenghua (Frontiers in Microbiology, 2023)
The special blood circulation, anatomy, and tissue structure of the spine may lead to significant differences in pathological features and drug resistance between spinal tuberculosis and pulmonary tuberculosis. Here, we collected 168 spinal tuberculosis cases and 207 pulmonary tuberculosis cases, and compared their clinical and pathological features as well as drug resistance. From the anatomical location, the highest incidence was of lumbar tuberculosis, followed by thoracic tuberculosis.PET-CT scans showed increased FDG uptake in the diseased vertebrae, discernible peripheral soft tissue shadow, visible internal capsular shadow, and an abnormal increase in FDG uptake. MRI showed infectious lesions in the diseased vertebral body, formation of paravertebral and bilateral psoas muscle abscess, and edema of surrounding soft tissues. As with control tuberculosis, the typical pathological features of spinal tuberculosis were chronic granulomatous inflammation with caseous necrosis. The incidence of granulomas was not statistically different between the groups. However, the proportions of caseous necrosis, acute inflammation, abscess, exudation, and granulation tissue formation in the spinal tuberculosis group were all significantly increased relative to the control tuberculosis group. Compared to the control tuberculosis group, the incidences of resistance to rifampicin (RFP) + isoniazid (INH) + streptomycin (STR) and INH + ethambutol (EMB) were lower in the spinal tuberculosis group, while the incidences of resistance to RFP+INH+EMB and RFP+EMB were higher. Moreover, we also found some differences in drugresistance gene mutations. In conclusion, there are noticeable differences between spinal Mycobacterium tuberculosis and pulmonary tuberculosis in pathological characteristics, drug resistance, and drug resistance gene mutations.